Curative Potentials of Garlic (Allium sativum) Extract against Di-(2-Ethylhexyl) Phthalate Induced Reproductive Toxicity in Female Mice: Amelioration of DEHP-induced toxicity by garlic extract - Sajida Batool; Riqza Aziz; Sitara Shameem; Marrium Shaheen; Saira Batool; Iqra Aslam; Fatima Iram (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
The present study was intended to find out the curative potentials of Garlic (Allium sativum) against di-(2-Ethylhexyl) phthalate (DEHP) induced toxicity in the reproductive system of female mice. Forty female mice were divided into four groups (n=10) as the (a) control group was given normal feed and drinking water, (b) aqueous garlic extract treated group (500 mg/kg), (c) DEHP group received 500 mg/kg in corn oil, and (d) DEHP + aqueous garlic extract each at a dosage of 500 mg/kg body weight. All treatments were given daily through oral gavage for 28 days. After completion of the experiment, all the animals were dissected through cervical dislocation to get reproductive organs. Collected organs were weighed and processed through the conventional histology technique of staining with eosin and hematoxylin. This study indicated that DEHP exposure caused a significant decrease (P<0.001) in body weight and weight of the complete female reproductive tract as compared to the control group, while the garlic co-administered group showed prominent improvement in body and organ weight when compared to only DEHP treatment. The adverse effect of DEHP on the histology of the ovary such as a decreased mean number of developing follicles, thin and irregular corona radiata, disruption of cumulus oophorus, and reduction in the size of the antral cavity of the tertiary follicle was observed. However, a significant recovery in the development of follicles was seen in DEHP plus garlic-treated group. DEHP plus garlic extract treatment showed protective effects on the uterus, such as a significant increase in the diameter of the uterus (P<0.001), muscularis, mean number of endometrial glands (P<0.001), and endometrial epithelial heights as compared to only DEHP exposed group. Hence, garlic extract showed significant ameliorative potential against DEHP-induced reproductive anomalies in female mice.